1997
DOI: 10.1080/15216549700203891
|View full text |Cite
|
Sign up to set email alerts
|

A study of the Na /H antiport in the archaeon Methanobacterium thermoautotrophicum strain ΔH

Abstract: SummaryThe ability of the cells of Mb. thermoautotrophicum strain AH to generate a proton gradient (driven by a concentration gradient of sodium ions) at pH 6.8 as well as at pH 8 was demonstrated. The electrogenic Na+/H + antiport responsible for this process was shown to be inhibited by EIPA and also by DCCD. Artificially increasing of intracellular concentration of Ca 2+ in these cells enhanced the Na+/IT antiport activity, while the lowering of external Ca 2+ by EGTA significantly decreased this activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The Na + /H + antiport activity was not inhibited either in the presence of 40 μM Co 2+ ions or 40 μM Ni 2+ (data not shown). These results specify that Ca 2+ transport does not play any role in Ca 2+ control of the Na + /H + antiport described earlier (Majerník et al , 1997). Furthermore, ATP synthesis driven by an electrogenic potassium efflux in the presence of either H + or Na + ions was not inhibited by 10 mM EGTA (Table 2).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The Na + /H + antiport activity was not inhibited either in the presence of 40 μM Co 2+ ions or 40 μM Ni 2+ (data not shown). These results specify that Ca 2+ transport does not play any role in Ca 2+ control of the Na + /H + antiport described earlier (Majerník et al , 1997). Furthermore, ATP synthesis driven by an electrogenic potassium efflux in the presence of either H + or Na + ions was not inhibited by 10 mM EGTA (Table 2).…”
Section: Resultssupporting
confidence: 90%
“…Further studies revealed that methane formation from H 2 +CO 2 is coupled to the generation of two primary ion gradients, an electrochemical proton gradient and an electrochemical sodium ion gradient (Müller et al , 1988; Kaesler & Schönheit, 1989; Thauer, 1990). It seems that Na + /H + antiport has a key function in this complex bioenergetic machinery via conversion of one of the gradients to the other in M. thermautotrophicus (Müller et al , 1987; Kaesler & Schönheit, 1989; Majerník et al , 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anaerobic conditions were maintained by a continuous flow of N 2 gas. pH changes were measured using semi‐micro glass pH electrode by pH meter (ORION) equipped with a recorder [20]. For the study of ATPase activity, Triton X‐100 permeabilised cells were prepared as described in [21].…”
Section: Methodsmentioning
confidence: 99%
“…Although many prokaryotic Na + /H + antiporters have been cloned and studied in antiporter deficient E. coli mutants [9–11], very little is known about antiporters from the archaeal kingdom. The only evidence for Na + /H + antiporters in archaea comes from studies using either intact cells or vesicles [12–14], but none of the genes has been cloned and studied in a heterologous system, yet.…”
Section: Introductionmentioning
confidence: 99%